If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3.6 = r + -2.3 Reorder the terms: 3.6 = -2.3 + r Solving 3.6 = -2.3 + r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1r' to each side of the equation. 3.6 + -1r = -2.3 + r + -1r Combine like terms: r + -1r = 0 3.6 + -1r = -2.3 + 0 3.6 + -1r = -2.3 Add '-3.6' to each side of the equation. 3.6 + -3.6 + -1r = -2.3 + -3.6 Combine like terms: 3.6 + -3.6 = 0.0 0.0 + -1r = -2.3 + -3.6 -1r = -2.3 + -3.6 Combine like terms: -2.3 + -3.6 = -5.9 -1r = -5.9 Divide each side by '-1'. r = 5.9 Simplifying r = 5.9
| -4x+6=2x+18 | | a^2-8=26 | | 8.2x+4=7.6x+10 | | x+3=-x-6 | | 64=-2r | | 8.2+4=7.6x+10 | | 9x^2=6-4x | | q+6whenq=12 | | 1-3/5+1/2= | | 2x^2-190x+2400=0 | | 0.50x+0.15(30)=46.5 | | -9c-5=13 | | z-7=14 | | -7=m(-6)+b | | 42+m=-21 | | -36+f=4 | | -2+3x=4x-7-x | | -1/2(6x+9)-(x-3/2)= | | 2+x=-(x+6) | | 2(13x-15)+3(x-19)=0 | | 2x+5+3x=15 | | h+4=-3 | | -4(3y-6)-y=-3(y-4) | | 2x^2-22x+28.5=0 | | 16+z=14 | | (x^2)-2x-35=0 | | 4*(x*4)=32 | | 5n-2m=8 | | -2x^2+7x+1=17 | | 6x+8+7x-5=180 | | -p+7=5-(9p+4) | | -3r=42 |